Survei Tingkat Kebugaran Jasmani Peserta Ekstrakurikuler Bela Diri Sekolah Menengah Kejuruan Negeri - Rahmawati, Dewi Fitri; Hariyanto, Eko (Sport Science and Health, 2020)
Abstract: The research aimed to determine the physical fitness level of the martial arts extracurricular members using a descriptive quantitative survey method with the independent variables: martial extracurricular (X) and the dependent variable level of physical fitness (Y). The research subjects were 25 participants. The results of the physical fitness test: (1) the level of physical fitness of jujitsu extracurricular with either 8 participants or 57.14% category and 6 participants or 42.86% moderate category. (2) the level of extracurricular physical fitness of the portion with either 2 participants or 18.18% categories, 3 participants or 27.27% in the moderate category, and 6 participants or 54.55% in poor category. Conclusion: the overall level of martial arts extracurricular fitness is in the good category, namely 40%.Â Abstrak: Penelitian bertutjuan mengetahui tingkat kebugaran jasmani peserta ekstrakurikuler bela diri menggunakan rancangan deskriptif kuantitatif metode survei dengan variabel bebas: ekstrakurikuler bela diri (X) dan variabel terikat tingkat kebugaran jasmani (Y). Subyek penelitian berjumlah 25 peserta. Hasil tes kebugaran jasmani: (1) tingkat kebugaran jasmani ekstrakurikuler jujitsu dengan kategori baik 8 peserta atau 57,14% dan kategori sedang 6 peserta atau 42,86%. (2) tingkat kebugaran jasmani ekstrakurikuler porsigal dengan kategori baik 2 peserta atau 18,18%, kategori sedang 3 peserta atau 27,27%, dan kategori kurang 6 peserta atau 54,55%. Simpulan: tingkat kebugaran jasmani ekstrakurikuler bela diri keseluruhan termasuk kategori baik yaitu sebesar 40%.